Risk and Protective Factors for Suicidality at 6-Month Follow-up in Adolescent Inpatients Who Attempted Suicide: An Exploratory Model - Consoli, Angèle (Can J Psychiatry, 2015)
OBJECTIVE: To assess risk and protective factors for suicidality at 6-month follow-up in adolescent inpatients after a suicide attempt. METHODS: One hundred seven adolescents from 5 inpatient units who had a suicide attempt were seen at 6-month follow-up. Baseline measures included sociodemographics, mood and suicidality, dependence, borderline symptomatology, temperament and character inventory (TCI), reasons for living, spirituality, and coping scores. RESULTS: At 6-month follow-up, 41 (38%) subjects relapsed from suicidal behaviours. Among them, 15 (14%) had repeated a suicide attempt. Higher depression and hopelessness scores, the occurrence of a new suicide attempt, or a new hospitalization belonged to the same factorial dimension (suicidality). Derived from the best-fit structural equation modelling for suicidality as an outcome measure at 6-month follow-up, risk factors among the baseline variables included: major depressive disorder, high depression scores, and high scores for TCI self-transcendence. Only one protective factor emerged: coping–hard work and achievement. CONCLUSION: In this very high-risk population, some established risk factors (for example, a history of suicide attempts) may not predict suicidality. Our results suggest that adolescents who retain high scores for depression or hopelessness, who remain depressed, or who express a low value for life or an abnormally high connection with the universe are at higher risk for suicidality and should be targeted for more intense intervention. Improving adolescent motivation in school and in work may be protective. Given the sample size, the model should be regarded as exploratory.